2010
DOI: 10.1111/j.1439-0396.2009.00946.x
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL ARTICLE: Physiological values and factors affecting the metacarpal bone density of healthy feedlot beef cattle as measured by dual-energy X-ray absorptiometry

Abstract: The metacarpal bone mineral density of 136 healthy feedlot beef cattle of four different breeds (Charolaise, Limousine, Irish Crossbreed and Slovakian Crossbreed) raised and fed on standard conditions was measured by means of a dual-energy X-ray absorptiometry technique in an ex vivo study design. The average reference values (mean ± SD) of bone mineral density (BMD) for animals aged between 12 and 22 months and weighing between 236 and 546 kg have been reported and the effects of (i) breed, (ii) gender, (iii)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Our results (Tables and and Fig. ) show that the density of the area of the tympanoperiotic bone, including the tympanic bulla, in a new born striped (1.596–1.841 g cm −2 ) or bottlenose (1.173–1.537 g cm −2 ) dolphin equals or surpasses that of the metacarpal bone of adult Perissodactyla ranging from 1.45 to 1.85 g cm −2 and from 1.25 to 1.40 g cm −2 in horses and cattle, respectively (Carstanjen et al, ; Zotti et al, ). These high values are the more convincing because the prolonged formalin fixation may alter BMD by reducing the Ca 2+ content (for specimen conditions see Tables and ), so the actual density measured in some of the dolphins may be underestimated.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Our results (Tables and and Fig. ) show that the density of the area of the tympanoperiotic bone, including the tympanic bulla, in a new born striped (1.596–1.841 g cm −2 ) or bottlenose (1.173–1.537 g cm −2 ) dolphin equals or surpasses that of the metacarpal bone of adult Perissodactyla ranging from 1.45 to 1.85 g cm −2 and from 1.25 to 1.40 g cm −2 in horses and cattle, respectively (Carstanjen et al, ; Zotti et al, ). These high values are the more convincing because the prolonged formalin fixation may alter BMD by reducing the Ca 2+ content (for specimen conditions see Tables and ), so the actual density measured in some of the dolphins may be underestimated.…”
Section: Discussionmentioning
confidence: 60%
“…In general, the regional deposition of biominerals during ontogeny reflects the requirement of each species after birth: so the large herbivores have highly dense distal bony segments of the limbs, necessary to stand and move shortly after birth. In fact, the bone density of the metacarpal bones in relation to body weight of the adult horse is one of the highest among terrestrial mammals (Carstanjen et al, ; Zotti et al, ) and thus is functional to the dynamic requirements of locomotion when the full weight of the body may be sustained by one limb at a time.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the extent of published studies covering the use of DXA with rodents we elected to avoid their inclusion in this chapter except in a few instances for comparison. DXA has been used with species of agricultural concern including sheep (Mercier et al, 2006;Ponnampalam et al, 2007;Pouilles et al, 2000;Turner et al, 1995a), pigs (Clarys et al, 2010;Elowsson et al, 1998;Lee et al, 2011;Losel et al, 2010;Lukaski et al, 1999;Mitchell et al, 1998;Nielson et al, 2004), horses (McClure et al, 2001;Secombe et al, 2002), goats (Corten et al, 1997), and cattle (Zotti et al, 2010). Additionally, DXA has been applied to wildlife such as the grizzly bear (Felicetti, 2003 as cited in Stevenson & van Tets, 2008).…”
Section: Dxa Use With Animalsmentioning
confidence: 99%
“…Even though there are benefits of the large scanner size for these applications, there are upper limits in body size that DXA can handle. Although DXA has been used previously with horses and cattle, its uses have been limited to analyses of bone density on excised bones (Secombe et al, 2002;Zotti et al, 2010). Currently, scanners are not large enough to allow for full-body scanning of larger animals, with the exception of carcass analysis.…”
Section: Sizementioning
confidence: 99%
“…Keene et al (2004) stated that "non-invasive imaging techniques are not sufficiently sensitive to detect changes in mineral content or composition of mature cows, and only modest changes in bone mineral can be observed with stage of lactation and parity". Zotti et al (2010) suggested that the main limitation to absorptiometry technology is the lack of reference values for bone mineral density in cattle, as it is the "gold standard" for evaluating the bone mineral density in humans.…”
Section: Bonementioning
confidence: 99%